Efektivitas Penyelenggaraan Pelayanan Terpadu Satu Pintu di Kota Tanjungpinang - ., Mulyadi (Universitas Internasional Batam, 2018)
One of the priorities of Joko Widodo's current administration is the public service sector, public service is the basic thing in the administration of the government to fulfill the needs of its people. The Tanjungpinang City Licensing Services Agency, as one of the regional apparatus organizations that has a service function, understands and encourages better service delivery. The method used is a quantitative approach that combines both qualitative and quantitative data inputs as well (mix method). Because in this study, the author moved from a case study that produced qualitative data input (human perception) with the help of a questionnaire. The Juridical Sociological Approach is aimed at reality by looking at the application of law (Das Sein) that is different from the desired legal rules (Das Sollen).